Analysis of Customer Behavior Using Cash Deposit Machine and BSI Smart in Langsa City - Mastura, Mastura; Ridwan, Achmad; Nurjanah, Nurjanah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Technological developments have also led Islamic Bank Indonesia to increase the efficiency of banking services by offering various digital transaction alternatives. The aim of this research is to analyze customer behavior and what factors influence customer behavior in using the Cash Deposit Machine (CDM) and BSI Smart in Langsa City. The research method used is descriptive qualitative to explore the behavior of Bank Syariah Indonesia customers with Cash Deposit Machine (CDM) and BSI Smart services in Langsa City. With the participation of 10 informants using the Snowball Sampling technique, primary data was obtained through interviews, supported by secondary data from journal literature. Data collection uses observation, interviews and documentation. The research results show that the behavior of Sharia Bank customers in Langsa City towards the use of Cash Deposit Machines (CDM) and BSI Smart shows adaptation to modern technology in financial activities. A total of 6 customers prefer CDM because of its speed, practicality, privacy and security. CDM user customers appreciate easy access to daily transactions. Meanwhile, 4 customers chose BSI Smart because of its flexibility in being able to carry out transactions in various locations without dependence on CDM machines. Factors that influence customer behavior using Cash Deposit Machines (CDM) and BSI Smart in Langsa City include security and privacy, perception of technology, personal factors and psychological factors. This research has a significant contribution to Bank Syariah Indonesia in developing optimal digital service strategies.